NEW INSIGHTS, OLD TEXTS CLERICAL FORMATION AND THE CAROLINGIAN RENEWAL IN HRABANUS MAURUS - Phelan, Owen M. (Traditio, 2016)
Hrabanus Maurus's De institutione clericorum is a masterpiece of clerical formation, emblematic of the Carolingian Renewal and esteemed by thinkers throughout the Middle Ages. In the third book, Hrabanus juxtaposes Augustine's teachings in De doctrina christiana with Gregory the Great's instruction in the Regula pastoralis to craft an original case for a close connection between wisdom and moral life in priestly training. Hrabanus's effort concretizes long-standing concerns of Carolingian reformers reiterated in landmark reform documents from the late eighth and early ninth centuries. Moreover, throughout his life, Hrabanus periodically returns to his work on priestly formation for words and ideas to undergird subsequent efforts at integrating education with pastoral practice in a variety of genres, including his model sermons, his encyclopedic commentary, and his handbook for missionary conversion. In addition to highlighting Hrabanus's individual genius as one who adroitly applies traditional authorities in novel ways to contemporary problems, this study illumines the crucial role played by monasteries like Fulda as engines for the Carolingian reform.